2019
DOI: 10.1002/ejic.201900712
|View full text |Cite
|
Sign up to set email alerts
|

Solution and Solid‐State Structure of the First NHC‐Substituted Rhenium Heptahydrides

Abstract: The structure of three new bis(N‐heterocyclic carbene) heptahydride rhenium complexes ([ReH7(NHC)2] with NHC= IMes (2b) (1,3‐bis(2,4,6‐trimethyl phenyl) imidazol‐2‐ylidene), IMesCl2 (4b) (4,5‐dichloro‐1,3‐dihydro‐1,3‐bis(2,4,6‐trimethyl phenyl)‐2H‐imidazol‐2‐ylidene) BIMes (5b) (1,3‐Bis(2,4,6‐trimethylphenyl)‐benzo imidazole ylidene), and of the known complex [ReH7(PPh3)2] (1) (bis(triphenyl phosphine)‐rhenium heptahydride), and the one of their labelled counterparts 2c‐d7, 4c‐d7, and 5c‐d7, were established i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…209 Finally, Various rhenium (V or VII) NHC complexes have been prepared, including water stable or 188 Re radiolabeled species. 210,211,212,213 In total, 10 technetium NHC complexes have been characterized by X-ray diffraction studies and the bond distances range from 2.07 to 2.23 Å. More than 165 examples of molecular structure of rhenium NHC complexes are known and bond distances range from 2.06 to 2.25 Å with a maximum at 2.14 Å (36 examples).…”
Section: B) Technetium and Rheniummentioning
confidence: 99%
“…209 Finally, Various rhenium (V or VII) NHC complexes have been prepared, including water stable or 188 Re radiolabeled species. 210,211,212,213 In total, 10 technetium NHC complexes have been characterized by X-ray diffraction studies and the bond distances range from 2.07 to 2.23 Å. More than 165 examples of molecular structure of rhenium NHC complexes are known and bond distances range from 2.06 to 2.25 Å with a maximum at 2.14 Å (36 examples).…”
Section: B) Technetium and Rheniummentioning
confidence: 99%
“…[ 37,38 ] Following a published procedure, we reacted the IMes free carbene with complex 1 to afford the complex ([IMes] 2 ReOBr 3 ) ( 2 ) in good yields (Scheme 1; SI S5 and S6). [ 39 ] For the synthesis of ([Py] 3 ReNOBr 2 ) ( 5 ), the second selected catalyst, we first explored the available synthesis already present in literature. Starting from the Re (II) paramagnetic complexes (ReNOBr 5 )(Et 4 N) 2 ( 3 ) and ([OPPh 3 ] 2 Re(NO)Br 3 ) ( 4 ), the groups of Ciani et al [ 40 ] and Machura et al [ 41 ] were able to synthesize the complex 5 .…”
Section: Resultsmentioning
confidence: 99%
“…Line shape fitting of dynamic NMR spectra [ 10 , 23 , 31 , 33 , 34 , 37 , 58 , 59 ], molecular modeling [ 22 , 27 , 35 , 36 ], and isotopic substitution [ 1 , 4 , 31 , 33 , 60 , 61 ] are the most commonly used techniques to examine the dynamic properties of rhenium polyhydride complexes. Longitudinal 1 H NMR relaxation measurements (T 1 ) of hydride ligand relaxations have been frequently used to explore the possibility of dihydrogen ligand coordination, but the technique has been shown to have issues that make it less than ideal [ 11 , 14 , 16 , 58 , 62 ].…”
Section: Characterization Of Dynamic Processes At Rhenium Polyhydride...mentioning
confidence: 99%
“…Dihydrogen is more frequently used to probe the nature of a reaction or decomposition mechanism than as an actual source for hydrogen atom exchange with the inner coordination sphere rhenium hydride ligands. Recently, it was demonstrated that HD will exchange into the coordination sphere of rhenium(VII) polyhydride complexes stabilized by NHC ligands [ 4 ].…”
Section: Dynamic Properties That Occur At Rhenium Polyhydride Complexesmentioning
confidence: 99%
See 1 more Smart Citation